De novo discovery of bicyclic cysteine-rich peptides targeting gasdermin D - Choi Yi Li; Yin Sun; Alexander A. Vinogradov; Hiroaki Suga (Proceedings of the National Academy of Sciences, 2026)
Gasdermin D (GSDMD) is the principal executor of pyroptosis, a form of proinflammatory programmed cell death misregulation of which is associated with numerous diseases. Despite significant interest, no specific GSDMD inhibitors have been developed for clinical use so far. Here, we developed a strategy to generate mRNA-displayed libraries of bicyclic cysteine-rich peptides (bCRP), and utilized these libraries to develop potent peptide ligands to full-length GSDMD using a two-stage discovery process. Initial hit compounds were de novo discovered from GSDMD affinity selections using Random Nonstandard Peptides Integrated Discovery system, and were then optimized using mRNA display-based saturation mutagenesis. The resulting bCRPs bound to full-length GSDMD (best K D = 125 nM) and stabilized it against cleavage by caspase proteases. The bCRPs prevented the pore formation in liposome leakage assays and inhibited the secretion of IL-1β and lactate dehydrogenase from pyroptotic THP-1 cells. The potency, high metabolic stability, and synthetic accessibility of the discovered compounds make them promising leads for the development of GSDMD-targeting therapeutics.